Antimicrobial use in livestock production systems (AMUSE Livestock) tool version 2 - CGIAR Research Program on Livestock (2019)
The first version of the survey tool has been revised based on the findings of cognitive interviews conducted with livestock keepers, with questions rephrased to ensure they convey the intended message and reordered into a more logical flow. The revised tool is being piloted in Kenya, Uganda and Burkina Faso.